Different Associations Between the IREB2 Variants and Chronic Obstructive Pulmonary Disease Susceptibility - Zeng, Qiaoli; Chen, Qikang; Zou, Dehua; Guo, Runmin; Xiao, Dawei; Jiang, Shaohu; Chen, Riling; Wang, Yajun; Ma, Guoda (Frontiers in Genetics, 2020)
Background: Iron responsive element binding protein 2 (IREB2) variants may be involved in the pathogenesis of chronic obstructive pulmonary disease (COPD). Recently, many studies have been performed IREB2 susceptibility variants including the rs2568494, rs2656069, rs10851906, rs12593229, rs13180 associated with COPD. However, inconsistent findings have been reported . The aim of our research was to determine the association of IREB2 SNPs with  COPD patients. Methods: A comprehensive meta-analysis was performed to accurately estimate the associationbetween the IREB2 variants and COPD among four different genetic models. Results: This meta-analysis included a total of 4096 patients and 5870 controls. Here, we investigated these 5 IREB2 variants identified COPD risk. Our results indicate that rs2568494 were associated with increased risk of COPD for the dominant model(AA+GA vs GG: OR = 1.15, 95% CI: 1.01–1.30, P = 0.029) ; rs2656069 were associated with decreased risk of COPD for the recessive model (GG vs AA+ AG:OR=0.59, 95%CI: 0.44–0.79; P=0.000), additive model (GGvsAA:OR=0.64, 95%CI: 0.44–0.93; P=0.020) and allele model (GvsA: OR=0.81, 95%CI: 0.67–0.99; P=0.037); and rs10851906 were associated with decreased risk of COPD for the recessive model (GGvsAA+AG:OR=0.68, 95%CI: 0.48–0.96; P=0.027). Conclusions: Our findings suggest that the IREB2 rs2568494 minor alleles A may be a genetic factor in susceptibility to COPD. In addition, the minor alleles G of rs2656069 and rs10851906 may have an apparently protective effect .